Giant fibroadenoma of the breast: a benign breast mass mimicking malignancy - Jabeen, Nusrat; Abdulla, Hussain Adnan; Abushwemeh, Mohamed Ayed; Alqaseer, Asma; Alrayes, Amal (International Surgery Journal, 2021)
Fibroadenoma is a common benign lesion of the breast that usually occurs in young females. Giant fibroadenoma of the breast is a rare benign pathology, which is defined as fibroadenoma greater than 5 cm in size and/or weighs more than 500 g. It is usually found in adolescent women. A 37-year-old woman undergoing treatment for infertility was referred to the breast clinic with an ulcerating left breast lump that had progressively increased in size. Examination showed a fungating left breast mass that obliterated the nipple-areola complex. Ultrasound showed a large soft tissue mass in the left breast with enlarged left axillary lymph nodes. Computed tomographic (CT) scan showed a 13×17 cm left breast mass. Core biopsy of this mass reported possibility of phyllodes tumor, while axillary fine-needle aspiration cytology (FNAC) showed no evidence of malignancy. Total mastectomy with immediate reconstruction using silicone implant was performed. Final histopathology reported giant fibroadenoma. Most cases on giant fibroadenoma reported in literature are limited to adolescent or young females, however, our patient was relatively old, which makes this a rare case.